A series of amide functionalized isoreticular metal organic frameworks - Keceli, E.; Hemgesberg, M.; Grünker, R.; Bon, V.; Wilhelm, C.; Philippi, T.; Schoch, Roland; Sun, Y.; Bauer, Matthias; Ernst, S.; Kaskel, S.; Thiel, Werner R. (Microporous and Mesoporous Materials)
Keywords: Mechanics of Materials; Condensed Matter Physics; General Materials Science; General Chemistry

Metastable metal imidazolates: development of targeted syntheses by combining experimental and theoretical investigations of the formation mechanisms - Schröder, Christian A.; Saha, Sanjib; Huber, Klaus; Leoni, Stefano; Wiebcke, Michael (Zeitschrift für Kristallographie - Crystalline Materials)
Abstract In this report, we summarize our experimental and theoretical investigations in the zinc(II) imidazolate, [Zn(im) 2 ], and zinc(II) 4,5-dichloroimidazolate, [Zn(dcim) 2 ], systems that have been published previously. This comprises a study on the thermodynamic stabilities of the two densest phases with coi and zni framework structures in the [Zn(im) 2 ] system including the discovery and characterization of a new [Zn(im) 2 ·0.5py]-neb phase (py = pyridine), a study on the mechanism of formation of the [Zn(im) 2 ]-zni phase as well as a study on the discovery and characterization of a new [Zn(dcim) 2 ]-SOD phase. In addition, we present as yet unpublished work. This concerns the discovery and characterization of a new [Zn(im) 2 ·0.5mor]-neb phase (mor = morpholine) and investigations of the mechanisms of crystallization of [Zn(im) 2 ·0.5py]-neb and [Zn(im) 2 ·0.5mor]-neb as well as an evalutation of time-resolved SAXS/WAXS data recorded in-situ during the formation of [Zn(im) 2 ]-zni.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science

Mechanistic Studies of Silica Polymerization from Supersaturated Aqueous Solutions by Means of Time-Resolved Light Scattering - Kley, M.; Kempter, A.; Boyko, V.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Monitoring the Coordination Modulator Shell at MOF Nanocrystals - Zacher, Denise; Nayuk, Roman; Schweins, Ralf; Fischer, Roland A.; Huber, Klaus (Crystal Growth & Design)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Innovative and Highly Productive Joining Technologies for Multi-Material Lightweight Car Body Structures - Meschut, G.; Janzen, V.; Olfermann, T. (Journal of Materials Engineering and Performance)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Basic Investigations of Non-Pre-Punched Joining by Forming of Aluminium Alloy and High Strength Steel with Shear-Clinching Technology - Merklein, Marion; Meschut, Gerson; Müller, Martin; Hörhold, Réjane (Key Engineering Materials)
Facing a decreasing amount of resources on the one hand and an increasing demand for comfort on the other, more and more attention is being paid to sustainability and care for the environment. Particularly in the automotive sector, lightweight design principles continue to prosper rapidly. As a result, adjusted materials for different applications were developed. Due to the formation of intermetallic phases, most multi-material mixes cannot be welded and require adapted joining technologies. Mechanical joining technologies such as self-piercing riveting and mechanical clinching have proven effective methods of joining lightweight materials like aluminium and ductile steels. New high-strength steels are increasingly used in crash-sections, where limited deformation under impact load is required. These hot stamped steels have a very low elongation at break and therefore a low formability. Currently there is no joining by forming technology without pre-punching available using these grades of steels on die-side. The newly developed shear-clinching process is one possible method of joining this kind of material without additional elements. The fundamental idea of shear-clinching is a single-stage process in which pre-punching of the die-side material is performed by indirect shear-cutting and subsequent forming of the upper layer into this hole. This would immensely enlarge the application segment of mechanical clinching even if hot stamped steels are positioned on die-side. Fundamental studies are required to ensure process reliability and it is necessary to break down the joining process into fragments, like pre-punching and clinching with pre-punched sheet, and superpose them to form the combined procedure shear-clinching. This paper presents a detailed investigation of the sub-process clinching with pre-hole.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

2-Hydroxyethylammonium iodide - Kohrt, Christina; Spannenberg, Anke; Werner, Thomas (Acta Crystallographica Section E Structure Reports Online)
In the crystal structure of the title salt, C 2 H 8 NO + ·I − , N—H...O, N—H...I and O—H...I hydrogen bonds lead to the formation of layers staggered along the c axis.
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

CuO and Co3O4 Nanoparticles: Synthesis, Characterizations, and Raman Spectroscopy - Rashad, M.; Rüsing, Michael; Berth, Gerhard; Lischka, K.; Pawlis, A. (Journal of Nanomaterials)
Copper oxide and cobalt oxide (CuO, Co3O4) nanocrystals (NCs) have been successfully prepared in a short time using microwave irradiation without any postannealing treatment. Both kinds of nanocrystals (NCs) have been prepared using copper nitrate and cobalt nitrate as the starting materials and distilled water as the solvent. The resulted powders of nanocrystals (NCs) were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and atomic force microscopy (AFM) measurements. The obtained results confirm the presence of the both of oxides nanopowders produced during chemical precipitation using microwave irradiation. A strong emission under UV excitation is obtained from the prepared CuO and Co3O4 nanoparticles. The results show that the nanoparticles have high dispersion and narrow size distribution. The line scans of atomic force microscopy (AFM) images of the nanocrystals (NCs) sprayed on GaAs substrates confirm the results of both X-ray diffraction and transmission electron microscopy. Furthermore, vibrational studies have been carried out using Raman spectroscopic technique. Specific Raman peaks have been observed in the CuO and Co3O4 nanostructures, and the full width at half maximum (FWHM) of the peaks indicates a small particle size of the nanocrystals.
Keywords: General Materials Science

Hierarchically structured copper gallium spinels through microwave hydrothermal methods - Conrad, Franziska; Bauer, Matthias; Weyeneth, Stephen; Zhou, Ying; Hametner, Kathrin; Günther, Detlef; Patzke, Greta Ricarda (Solid State Sciences)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Increasing the Dimensionality of Quantum Walks Using Multiple Walkers - Rohde, Peter P.; Schreiber, Andreas; Štefaňák, Martin; Jex, Igor; Gilchrist, Alexei; Silberhorn, Christine (Journal of Computational and Theoretical Nanoscience)
Keywords: Electrical and Electronic Engineering; Computational Mathematics; Condensed Matter Physics; General Materials Science; General Chemistry

Korrosionsverhalten binärer Magnesium-Zink-Legierungen in salzhaltigen Medien - Hoyer, Kay-Peter; Angrisani, Gian Luigi; Klose, Christian; Bach, Friedrich-Wilhelm; Hassel, Thomas (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Structural Evolution in the Isotropic Channel of a Water–Nonionic Surfactant System That Has a Disconnected Lamellar Phase: A 1H NMR Self-Diffusion Study - Stubenrauch, Cosima; Kleinschmidt, Felix; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Benign Catalysis with Iron: Unique Selectivity in Catalytic Isomerization Reactions of Olefins - Jennerjahn, Reiko; Jackstell, Ralf; Piras, Irene; Franke, Robert; Jiao, Haijun; Bauer, Matthias; Beller, Matthias (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Impact of Sodium Polyacrylate on the Amorphous Calcium Carbonate Formation from Supersaturated Solution - Liu, J.; Pancera, S.; Boyko, V.; Gummel, J.; Nayuk, R.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Einfluss der Oberflächenbehandlung auf das Korrosionsverhalten von Magnesiumlegierungen - Hoyer, Kay-Peter; Hassel, Thomas; Bach, Friedrich-Wilhelm (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Molecular Recognition with 2,4-Diaminotriazine-Functionalized Colloids - Bayer, Frank M.; Tang, Mingxue; Michels, Rolf; Schmidt, Claudia; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Spin resolved photoelectron spectroscopy of [Mn6IIICrIII]3 +single-molecule magnets and of manganese compounds as reference layers - Helmstedt, Andreas; Müller, Norbert; Gryzia, Aaron; Dohmeier, Niklas; Brechling, Armin; Sacher, Marc; Heinzmann, Ulrich; Hoeke, Veronika; Krickemeyer, Erich; Glaser, Thorsten; Bouvron, Samuel; Fonin, Mikhail; et al. (Journal of Physics: Condensed Matter)
Keywords: Condensed Matter Physics; General Materials Science

Liquid Crystal/Polymer Composites: Kinetic Study of the Grating Formation in Holographic Polymer-Dispersed Liquid Crystals - Redler, Andreas; Hoischen, Andreas; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Electrooptic Switching in Graphene-Based Liquid Crystal Cells - Wahle, Markus; Kasdorf, Olga; Kitzerow, Heinz-Siegfried; Liang, Yanyu; Feng, Xinliang; Müllen, Klaus (Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Molecular Recognition with 2,4-Diaminotriazine-Functionalized Colloids - Bayer, Frank M.; Tang, Mingxue; Michels, Rolf; Schmidt, Claudia; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science